Long‐term efficacy and predictive correlates of response to nivolumab in Japanese patients with esophageal cancer. Issue 5 (29th April 2020) - Kato, Ken; Doki, Yuichiro; Ura, Takashi; Hamamoto, Yasuo; Kojima, Takashi; Tsushima, Takahiro; Hironaka, Shuichi; Hara, Hiroki; Kudo, Toshihiro; Iwasa, Satoru; Muro, Kei; Yasui, Hirofumi; et al.
Abstract: The long‐term efficacy of nivolumab in esophageal squamous cell carcinoma and its association with disease biomarkers are currently not well known. Therefore, we investigated the association in Japanese patients with treatment‐refractory advanced esophageal cancer who participated in an open‐label, single‐arm, multicenter phase II study. Patients received nivolumab 3 mg/kg i.v. every 2 weeks until disease progression or unacceptable toxicity, and were followed up for 2 years after the initial dosing of the last patient. Archival tissue samples were collected before treatment and analyzed for programmed death ligand‐1 (PD‐L1) and CD8 + status of tumors and tumor‐infiltrating lymphocytes (TILs) and human leukocyte antigen class 1. Efficacy end‐points included objective response rate (ORR), overall survival (OS), progression‐free survival (PFS), time to response, and duration of response. Of 65 enrolled patients (83% male), 64 were evaluable for efficacy and 41 (63%) for biomarkers. The ORR, median OS, and survival rate were 17.2%, 10.78 months, and 17.2%, respectively. Time to response was 1.45 months and duration of response was 11.17 months. The PD‐L1 positivity of tumor cells was possibly associated with better PFS (2.04 vs 1.41 months, cut‐off 1%) and OS (11.33 vs 6.24 months, cut‐off 1%). Median OS was prolonged in patients with a median number of TILs greater than 63.75% vs 63.75% or less (11.33 vs 7.85 months). Nivolumab showed continued long‐term efficacy, as seen by the stability of PFS and OS, in Japanese patients with esophageal squamous cell carcinoma. Further investigation of PD‐L1 tumor expression and TILs as potential biomarkers for predicting patients likely to benefit from nivolumab therapy is warranted. Abstract : An exploratory biomarker analysis was undertaken in Japanese patients with treatment‐refractory advanced esophageal cancer who were receiving nivolumab during the extension of a multicenter phase II study. Nivolumab showed continued efficacy in Japanese patients with esophageal squamous cell carcinoma, and the biomarker analysis suggested that higher levels of tumor‐infiltrating lymphocytes, especially CD8 + cells, could be associated with longer overall survival.